2021
DOI: 10.1371/journal.pone.0246691
|View full text |Cite
|
Sign up to set email alerts
|

Predicting major bleeding among hospitalized patients using oral anticoagulants for atrial fibrillation after discharge

Abstract: Aim Real-world predictors of major bleeding (MB) have been well-studied among warfarin users, but not among all direct oral anticoagulant (DOAC) users diagnosed with atrial fibrillation (AF). Thus, our goal was to build a predictive model of MB for new users of all oral anticoagulants (OAC) with AF. Methods We identified patients hospitalized for any cause and discharged alive in the community from 2011 to 2017 with a primary or secondary diagnosis of AF in Quebec’s RAMQ and Med-Echo administrative databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Indeed, in these settings, extreme regression coefficient estimates and very wide confidence intervals can be obtained. The Firth’s model has been successfully applied in different clinical fields, for example to predict major bleeding among patients using anticoagulants, to identify rare anaesthesia-related risk factors in children and to predict rare adverse events occurrence after vaccination 39 41 . At the best of our knowledge there are no applications of this model to predict CTCAE in GEPTNET patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in these settings, extreme regression coefficient estimates and very wide confidence intervals can be obtained. The Firth’s model has been successfully applied in different clinical fields, for example to predict major bleeding among patients using anticoagulants, to identify rare anaesthesia-related risk factors in children and to predict rare adverse events occurrence after vaccination 39 41 . At the best of our knowledge there are no applications of this model to predict CTCAE in GEPTNET patients.…”
Section: Discussionmentioning
confidence: 99%
“…29 Other than HASBED, we assessed variables that showed to be significantly related to GI bleeding were age >85 years, history of GI disease, history of bleeding, peripheral artery disease and myocardial infarction. Others have reported that risk factors for bleeding other than those assessed by the HASBED score might also come to play, 30 but further research is needed for confirmation. The gender effect was not found to interact with bleeding outcomes when HASBLED ≥4 while age attenuated the benefit of DOACs over warfarin.…”
Section: Discussionmentioning
confidence: 99%
“… 2 This appears especially promising with regard to the heterogeneous group of AF patients who are generally older and present with a large case-mix variability. 41 Although there are many examples of prognostic models for stroke 27 or bleeding 44 in AF patients, it is not clear how these models can be used for (within-class) DOAC treatment decision making (let alone combined consideration of both aspects). For this, our approach provides a straightforward path using well-established variables that have previously been shown to be prognostic or determine treatment decisions 46 and are largely available in routine clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the stroke models performed better than the bleeding models (see Figure 1A), possibly because many co-medications (including temporary or over-thecounter drugs) were not available in the present variables. 44 Nevertheless, the combined consideration of the composite endpoint (stroke and major bleeding) was impressively successful after weighting both aspects (and the sheer number of far more bleeding events than strokes may certainly have contributed to the significant result). Although our innovative approach overlaps only in small parts with previous work, consensus criteria for treatment-guiding risk modeling can be discussed.…”
Section: Discussionmentioning
confidence: 99%